REFLEXÕES SOBRE A ROMANIZAÇÃO DE BALSA - Mendes, Norma Musco (PHOÎNIX, 2020)
This paper discusses the character and features of Romanization in the Principate through a case study. Archaeological evidence from the city of Balsa in Algarve confirm the development of the pre-existing economic practices and the enrichement of the indigenous leading circles.